LITERATURE AND CINEMA: PROPOSAL FOR A COMPARATIVE INTERTEXTUAL DIALOGUE READING OF DON QUIXOTE AND SANCHO PANÇA AS IMAGES - León, Italo Oscar Riccardi (Revista (Entre Parênteses), 2020)
In the context of intertextual comparative dialogical relations that permeate the interfaces between literature and cinema, emerged the interest in studying the characters of Don Quixote and Sancho Panza, as emblematic images of the classic Hispanic work written by Miguel of Cervantes The ingenious gentleman Don Quixote de la Mancha, published in the seventeenth century, and also in the film version Don Quixote of the Russian filmmaker Gregory Kozintsev, produced in the fifties, with the main purpose of asking for an intertextual comparative look that might re-signify them by revisiting them while reading images (PALMA, 2004; STAM, 2008 and BAULER, 2013). This article discusses the approaches of literature and cinema as configurations of artistic language and, soon after, aims to examine and conceptualize the image as a visual representation and a bearer form of thought (SANTAELLA 1992/1993; PAZ, 2003 and SAMAIN, 2012) to analyze, afterwards, some significant images of Don Quixote and Sancho Panza who own an ambivalent role that captivates until today (NABOKOV, 2009; VARGAS LLOSA, 2010; BORGES, 2011), whose perspectives of analysis, among some of the authors approached, emphasize the need for another contemporary look at the interpretation or reading approach of images of artistic works that fit into the intertextual theoretical and dialogical comparative propositions of literature and other arts or other semiotic systems.